PROSPECTS OF OBTAINING UNIFORM SEED PROGENY OF EVERBEARING GARDEN STRAWBERRY - S. O. Baturin; I. K. Apolinarieva; A. A. Kuzmina (Вавиловский журнал генетики и селекции, 2015)
It is difficult to reach seed uniformity in Fragaria × ananassa Duch. (2n = 8x = 56) because of the high ploidy level of this species and polysomic inheritance of characters, including reproductive ones, and, correspondingly, to raise varieties propagating by seeds. The present work demonstrates efficiency of line crossings for achieving uniformity within everbearing strawberry seed progeny. Examination of three progeny lines resulting from line crossings of everbearing garden strawberry testified uniformity of major biomorphological traits. The seedlings were capable to produce yield four to five months after germination, which allows harvesting berries in West Siberia in August, September, and, partially, in October.